Public health law and ethics : a reader - Gostin, Lawrence O. (Lawrence Ogalthorpe); Wiley, Lindsay F., 1977- (University of California Press, 2018)
"Public Health Law and Ethics: A Reader, 3rd Edition probes the legal and ethical issues at the heart of public health through an incisive selection of judicial opinions, scholarly articles, and government reports. Crafted to be accessible to students while thorough enough to be used by practitioners, policy makers, scholars, and teachers alike, the reader can be used as a stand-alone resource, or alongside the internationally acclaimed Public Health Law: Power Duty, Restraint, 3rd Edition. This third edition reader includes discussions of today's most pressing health threats, such as chronic diseases, emerging infectious diseases, antimicrobial resistance, biosecurity, opioid overdose, gun violence, and health disparities"--Provided by publisher